Strategi dan Media Scaffolding pada Pembelajaran Berbasis Inkuiri - Purtadi, Sukisman; Suyanta, Suyanta; Rohaeti, Eli (LPPM Universitas Negeri Jakarta, 2023)
This literature review aims to analyze the forms of scaffolding strategies and their learning media used in inquiry-based learning (PBI). Scaffolding is a type of guidance given to students in the learning process with many types and strategies that are adapted to their learning objectives. the right scaffolding strategy will improve learning outcomes. Therefore, it is necessary to do a literature review to be able to determine the scaffolding strategy to be used. The study was conducted on 43 research articles that had been published from 2015 to 2022. These articles were selected based on the systematic steps of determining study questions, selecting publications, filtering articles based on keywords. Furthermore, the selected articles were reviewed with the aid of Atlasti.9. The results of this study concluded that the question prompt is a common strategy in guiding students to inquiry. Some of the media used to help students are worksheets and computer-assisted media.